2017
DOI: 10.1016/j.kint.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 amplification limited to the circulation does not protect mice from development of diabetic nephropathy

Abstract: Blockers of the renin-angiotensin system are effective in the treatment of experimental and clinical diabetic nephropathy. An approach different from blocking the formation or action of angiotensin II(1-8) that could also be effective involves fostering its degradation. Angiotensin converting enzyme 2 (ACE2) is a monocarboxypeptidase than cleaves angiotensin II (1-8) to form angiotensin (1-7). Therefore, we examined the renal effects of murine recombinant ACE2 in mice with streptozotocin-induced diabetic nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 71 publications
(116 reference statements)
7
83
0
Order By: Relevance
“…The literature on plasma ACE2 is limited, and there are some reports showing increased levels of circulating ACE2 in patients with type 1 diabetes and vascular complications (45), or in patients with CKD (39). However, we did not detect plasma ACE2 in our patient population using a fluorogenic substrate assay and mass spectrometric analysis, which is in agreement with recent findings in diabetic animal models (2,41,50) and with clinical findings in patients with CKD (32). Therefore, our results support involvement of renal pathologies resulting in urinary ACE2 excretion.…”
Section: Discussionsupporting
confidence: 91%
“…The literature on plasma ACE2 is limited, and there are some reports showing increased levels of circulating ACE2 in patients with type 1 diabetes and vascular complications (45), or in patients with CKD (39). However, we did not detect plasma ACE2 in our patient population using a fluorogenic substrate assay and mass spectrometric analysis, which is in agreement with recent findings in diabetic animal models (2,41,50) and with clinical findings in patients with CKD (32). Therefore, our results support involvement of renal pathologies resulting in urinary ACE2 excretion.…”
Section: Discussionsupporting
confidence: 91%
“…The extracellular part of ACE2 (1-740 AA), here referred as "native" ACE2, contains the catalytic domain and is fully catalytically active. In our previous studies, the administration of native rACE2 (1-740 AA) resulted in a marked increase in circulating ACE2 activity, but neither kidney nor urinary ACE2 activity increased [6,12,13].…”
Section: Introductionmentioning
confidence: 82%
“…The lack of increase in urinary ACE2 activity after injection of native rACE2 was attributed to the lack of glomerular filtration of native rACE2, consistent with its large molecular size of 100-110 kDa [12,13]. While markedly increased circulatory levels of ACE2 activity after native rACE2 administration are capable of effectively lowering blood pressure in models of Ang II-induced hypertension [6,7,14] or renin overexpression in the circulation [15], their use is not suitable for treatment of other forms of kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 inhibition in the streptozotocin-induced diabetic mouse model showed increased urine albumin to creatinine ratio as well as expansion of the glomerular matrix relative to mice with diabetes alone [46]. More recently, ACE2 knockout in diabetic mice was associated with increased blood pressure, mesangial matrix expansion, podocytes loss, and renal fibrosis including increased α-SMA accumulation and collagen deposition when compared to wild-type diabetic mice [47, 48••]. Importantly, the protective effects of ACE2 expression have also been found to be specific to the kidney.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Further support for the cross talk between renal ACE and ACE2 was demonstrated by the finding of increased renal ACE expression during ACE2 inhibition [46]. However, at least one recent study using the ACE2 knockout mouse found that while ACE2 deletion increased systemic ACE expression and worsened nephropathy, renal cortical ACE was in fact decreased [48••]. These findings emphasize the importance of the ongoing investigations into interactions of ACE and ACE2 in diabetic kidney disease.…”
Section: Diabetic Nephropathymentioning
confidence: 99%